Arsenic Distribution and Adsorption Behavior in the Sediments of the Daliao River System in China. (1st August 2013) - Wang, Shiliang; Lin, Chunye; He, Mengchang; Liu, Xitao; Liu, Shaoqing
ABSTRACT: : This study investigated the arsenic (As) distribution and adsorption behavior in sediments of the Daliao River System (DRS). Results indicated that the total As was 2.6–83.1 mg kg −1 in the sediments of the DRS. The pseudo‐first order model and intra‐particle diffusion model give a good fit of the experimental kinetics data for As, indicating that particle diffusion mechanism may not be the rate controlling step while this mechanism is involved. By comparing the zero equilibrium As concentration (EAsCo ) with the actual As concentration in the overlying water of the DRS, all the sediments showed a trend of releasing As. Arsenic exhibited strong adsorption on sediment at pH 4.5–7. Arsenic retention by sediment was much enhanced by Ca 2+ compared to Na + . More As was desorbed by phosphate at low and high pH extremes. The added or sorbed As was mainly transferred to the specifically sorbed fraction and amorphous Fe (Al) oxyhydroxides bound fraction, indicating Fe oxides are a major sorbent of As in sediment.